Remarks on Some Recent Fixed Point Results on Quaternion-Valued Metric Spaces - Ravi P. Agarwal; Hamed H. Alsulami; Erdal Karapınar; Farshid Khojasteh (Abstract and Applied Analysis)
Very recently, Ahmed et al. introduced the notion of quaternion-valued metric as a generalization of metric and proved a common fixed point theorem in the context of quaternion-valued metric space. In this paper, we will show that the quaternion-valued metric spaces are subspaces of cone metric spaces. Consequently, the fixed point results in such spaces can be derived as a consequence of the corresponding existing fixed point result in the setting cone metric spaces.